Characterizing Pediatric Non-Malarial Fever and Identifying the At-Risk Child in Rural Malawi - Teresa Bleakly Kortz MD, MS; Alden Blair PhD; Ellen Scarr PhD, RN, FNP; Andrew Masozi Mguntha BEd; Gama Bandawe PhD; Ellen Schell PhD, RN; Sally Rankin PhD, RN; Kimberly Baltzell PhD, MS, RN, FAAN (SAGE Publishing, 2018)
Objective . To characterize children with non-malarial fever at risk of nonrecovery or worsening in rural Malawi. Methods . This is a subgroup analysis of patients ≤14 years of age from a prospective cohort study in non-malarial fever subjects (temperature ≥37.5°C, or fever within 48 hours, and malaria negative) in southern Malawi cared for at a mobile clinic during the 2016 dry (August to September) or wet (November to December) season. Data collection included chart review and questionnaires; 14-day follow-up was conducted. We conducted univariate descriptive statistics on cohort characteristics, bivariate analyses to examine associations between characteristics and outcomes, and multivariate logistic regressions to explore factors associated with nonrecovery. Results . A total of 2893 patients were screened, 401 were enrolled, 286 of these were children, and 280 children completed follow-up. Eighty-seven percent reported symptom resolution, 12.9% reported no improvement, and there were no deaths or hospitalizations. No improvement was associated with dry season presentation (42.6% vs 75.0%, P < .0003), >2 days of symptoms (51.6% vs 72.2%, P = .03), and food insecurity (62.3% vs 86.1%, P = .007). Dry season subjects had a 4.35 times greater likelihood of nonimprovement (95% confidence interval [CI] = 1.96-11.11). Household food insecurity and being >2 hours from a permanent clinic were associated with no improvement (adjusted odds ratio [AOR] = 4.61, 95% CI = 1.81-14.29; and AOR = 2.38, 95% CI = 1.11-5.36, respectively). Conclusion . Outcomes were generally excellent in this rural, outpatient pediatric cohort, though risk factors for nonrecovery included food insecurity, access to a standing clinic, and seasonality. Ideally, this study will inform clinic- and policy-level changes aimed at ameliorating the modifiable risk factors in Malawi and throughout rural Africa.